(untitled) (Universal International Scientific Journal, 2026)
: This article covers the theoretical and practical aspects of the psychological approach aimed at studying the personality and mental activity of mentally retarded children. The issues of the comprehensive study of the mental activity of mentally retarded children - perception, attention, memory, thinking and speech processes, as well as personality traits are analyzed. The article reveals the importance of an individual approach, the organization of psychocorrectional work, and the role of the psychological approach in ensuring the social adaptation of mentally retarded children.